Public Support for Feed-in-Tariff and Net Energy Metering Policies in Malaysia: The Role of Policy Information - Fatimah Azzahraa' Mohd Sobri; Mariani Ariffin; Amir Hamzah Sharaai; Mohd Amran Radzi (International Journal of Renewable Energy Development, 2022)
Renewable energy (RE) policies have proven to be an effective tool for implementing RE. Despite various policies introduced, the RE deployment in Malaysia has been weak, especially individual RE uptake. Lack of policy support has been linked with inadequate policy awareness and information based on the knowledge deficit theory. This study investigates the support for the Feed-in-Tariff (FiT) and Net Energy Metering (NEM) policy of individual solar photovoltaic (PV) technology among landed residents in Malaysia and the effect of information provision on policy support. A Solomon-four-group design was employed to measure policy support and test the relationship between information provision and policy support using a set of Likert scale questionnaires and a poster of FiT and NEM policy prepared in layman's terms as an intervention. Results show that majority of the residents agree with the environmental mission of the policy, except for the reduction of fossil fuel usage. For the economic aspect, the residents prefer a fixed rate for RE produced and generally agreed that high electricity consumers should pay for the RE fund. However, residents were less enthusiastic about the percentage deducted from electricity bills and the 'high electricity consumer' baseline.  There was a significant difference between items scores at pre and post-test when given the intervention, in line with the deficit theory. Therefore, policy information should be communicated strategically, focusing on thepolicy's social and economic components that have the greatest influence on Malaysians.